Conflicts of Social Class in Movies - Sopa Marwati; Nurholis Nurholis; Hasbi Assiddiqi (Universitas Islam Negeri Sunan Gunung Djati, 2021)
Social conflict happens due to diversities of opinion, culture, and ideology in the certain society. It can be discovered in every stratum of society level, social conflict can occur in the upper, middle and lower class. This study explained social class conflicts which were taken from two movies: Parasite (2019) and Joker (2019). This study uses a comparative literary theory by Sussan Bassnet. Th study also used focused on the social class conflict theory by Lewis Coser and the classification of people by Karl Max. The method used in this research is descriptive in technique of analyzing the data was obtaining by categorizing, describing and interpreting the data, then making conclusion. The result showed that in the Parasite and the Joker movies contained of social class conflict, it occurred inter classes of people in a society. based on analysis, it concluded that both of the movie has differences in the social class conflict and the causes of the conflict itself. However, both movies have the same consequences of the conflict. In the Parasite movie social class conflict occurred inter the lower class. While, in the Joker movie, the social class conflict occurred between the upper and lower class.Keywords: social class conflcit, comparative literature, Parasite, Joker